Effects of cognitive remediation therapy on neurocognition and negative symptoms in schizophrenia: an Italian naturalistic study. Issue 1 (2nd January 2017) - Lanfredi, Mariangela; Deste, Giacomo; Ferrari, Clarissa; Barlati, Stefano; Magni, Laura Rosa; Rossi, Roberta; de Peri, Luca; Bonomi, Marco; Rossi, Giuseppe; Vita, Antonio
ABSTRACT: Introduction : Cognitive remediation therapy (CRT) has been reported to positively affect neurocognitive processes among patients with schizophrenia; however, the degree to which changes in cognition is linked to improved clinical symptoms, remains poorly understood. The current study aimed to investigate whether cognitive gains were associated to improvements in negative symptoms' severity in patients with schizophrenia living in two Italian psychiatric facilities. Methods : Patients with a diagnosis of schizophrenia were consecutively assigned to CRT ( n  = 33) and compared with an historical control group ( n  = 28). Assessments were performed at baseline and post-treatment using a neuropsychological battery (Trail Making Test A and B, Self-Ordered Pointing Task, California Verbal Learning Test), along with clinical and functioning measures. Results : Visual attention (TMT-A score change) was found as the only significant predictor of improvement in negative symptoms subscale of the Positive and Negative Syndrome Scale. Furthermore, a mediation path analysis confirmed that better performance in visual attention acts as mediator of the positive association between CRT intervention and lower post-treatment negative symptoms score. Conclusions : CRT can have a positive impact on a measure of visual attention in patients with schizophrenia and on negative symptoms reduction that is mediated by this significant intervention effect.